Leviathan in cyberspace: how to tax e-commerce - Jürgen Stehn (Institut für Weltwirtschaft (IfW), 2002)
Because of the upswing in electronic commerce via the Internet, governments in the European Union and the United States have been discussing the shaping of an effective system of turnover taxation in cyberspace since the late 1990s, but have failed to agree on a definite tax system. An analysis of the various possible approaches to turnover taxation in cyberspace shows that the main challenge of the new economy is to effectively cope with business-to-consumer (B2C) transborder trade in digital on-line goods and services. However, the traditional systems of turnover taxation that are based on the country-of-destination principle such as the transitional system of the European Union, the sales tax system, the community principle, and the VIVAT and CVAT approaches give rise to several surveillance, efficiency, incentive, and identification problems in taxing B2C e-commerce. This is also the case with the more innovative proposals that have been made with regard to the taxation of B2C transborder trade in digital on-line goods, such as the German payment flow proposal, the U.S. e-card proposal, the modified country-of-origin proposal of the EU Commission, or the bit tax proposal. As a consequence, there are only two appropriate approaches to deal with the special characteristics of transborder trade in cyberspace: the country-of-origin principle combined with a taxation of digital goods and services at the physical location of producers, and the community principle in combination with a withholding tax (WITHVAT). Under the country-of-origin principle, exports are taxed at the rate of the country of origin and imports are free of tax. The taxation of goods turnovers at the physical location of the firms involved could at least partly prevent the transfer of Internet firms to low-tax countries. The main advantage of the country-of-origin principle is that it does not require any transborder tax adjustment and that it is also a suitable and effective approach for the turnover taxation of traditional off-line and on-line goods. However, the country-of-origin principle requires an administratively burdensome central clearinghouse system in order to guarantee the regional fiscal assignment according to the countryof- destination principle as demanded by the governments of the EU member states. Under the WITHVAT system, exports of digital on-line goods are taxed at the rate of the country of destination and consumers are responsible for passing the tax funds on to their national tax authorities. In order to set incentives for consumers to correctly report their digital on-line purchases to national tax authorities, all suppliers of digital online goods would be forced to add a withholding tax that equals the highest VAT rate of all countries participating in the transborder VAT system to any sales to consumers. Consumers would get a refund according to the difference between the withholding tax and the tax rate of the country of destination if they presented the bills to their national tax authorities. The main advantage of the WITHVAT approach is that it does not need a central clearinghouse mechanism, because decentralized clearing is endogenous in the system. However, the WITHVAT approach may give rise to an unspecifiable obstacle to e-commerce and is not a suitable approach for the taxation of traditional off-line and on-line goods.
Keywords: 330; E-Business; Elektronisches Produkt; Elektronische Informationsdienstleistung; Umsatzsteuer; Einfuhrumsatzsteuer; Optimale Besteuerung; Steuersystem; Theorie